EFL LEARNER’S PERSPECTIVE ON THE IMPORTANCE OF NON VERBAL COMMUNICATION WITHIN CLASSROO M CONVERSATION - Indah Sekar Pertiwi; Lilia Indriani (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
Communication is the way people deliver a message from the speaker to the receiver. Nonverbal communication is a form of silent language is used to deliver the message without using words. Nonverbal communication has essential roles in classroom interaction. Many researchers did a study about nonverbal communication in the teaching process. However, the study of EFL learner’s perspectives on nonverbal communication received little attention. In relation, the recent study would like to investigate the EFL learner's perspective toward non-verbal communication in classroom communication. In this research, the researcher used a descriptive qualitative approach with the questionnaire. EFL learners at Tidar University were adopted as participants in this research. The result shows that Nonverbal communications in the form of eye contact, mimics, and body language play essential roles in classroom conversation as the source of motivation and concentration. The importance of nonverbal communication can be aware for the teacher to create a better environment in classroom interactions.